Determinan Risiko Kematian Pasien Covid-19 - Mochammad Yusuf Maulana; I Made Arcana (Politeknik Statistika STIS, 2022)
The Covid-19 pandemic in Indonesia in the middle of 2021 showed an increase in the number of people exposed to the corona virus and the number of deaths among Covid-19 patients. A relatively similar situation also occured in Tegal City, where the risk of death for Covid-19 patients was quite high. This study aims to identify variables that significantly affect the risk of death among Covid-19 patients based on patient medical record data in period of January to August 2021 at Kardinah Hospital, which is the education hospital and Covid-19 first-line referral hospital in Tegal City. A total of 477 patients Covid-19 hospitalization was the subject of observation in this study. The analytical method applied was survival analysis by implementing the Weibull Proportional Hazard (PH) model whose best model was based on the smallest AIC value. The results showed that the highest level of risk of death occurred in female patients who were short of breath, which was 2.9 times the risk of death experienced by female patients who were not short of breath.